2021
DOI: 10.1177/0964528421997155
|View full text |Cite
|
Sign up to set email alerts
|

Additional value of auricular intradermal acupuncture alongside selective serotonin reuptake inhibitors: a single-blinded, randomized, sham-controlled preliminary clinical study

Abstract: Background: To evaluate the antidepressant effects of auricular intradermal acupuncture (AIA) of areas innervated by both the auricular branch of the vagus nerve and the trigeminal nerve. Methods: Forty-nine patients with depression were randomly allocated into an AIA group ( n = 25) and a sham AIA group ( n = 24). Both groups received selective serotonin reuptake inhibitors (SSRIs) as conventional treatment. The AIA group received AIA stimulation, and the sham AIA group received sham AIA, which constituted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
(33 reference statements)
0
7
0
1
Order By: Relevance
“…In the case of relaxation, the auricular branch of the vagus nerve is stimulated during treatment, leading to an increase in parasympathetic nerve activity and modification of both autonomic and central nervous system activity [36]. The representative acupoints for relaxation are MA-TF1 and Sympathetic (MA-AH6), and auricular acupressure applied to auricular acupoints has various positive effects including improvement in quality of sleep, and reduced blood pressure [37][38][39]; auricular acupuncture also reduces symptoms of depression [40].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of relaxation, the auricular branch of the vagus nerve is stimulated during treatment, leading to an increase in parasympathetic nerve activity and modification of both autonomic and central nervous system activity [36]. The representative acupoints for relaxation are MA-TF1 and Sympathetic (MA-AH6), and auricular acupressure applied to auricular acupoints has various positive effects including improvement in quality of sleep, and reduced blood pressure [37][38][39]; auricular acupuncture also reduces symptoms of depression [40].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to treatment with SSRIs alone, AIA demonstrates added therapeutic benefits in the management of patients suffering from MDD. 52 The acupoints that have been determined to be commonly utilized in the treatment of MDD have been identified by our research team through the process of data mining. 53 The most frequently used acupoints are Baihui (GV20), Taichong (LR3), Neiguan (PC6), Sanyinjiao (SP6), Yintang (GV29), and Shenmen (HT7).…”
Section: Methodsmentioning
confidence: 99%
“…Another investigation into patients with sleep disorders had significantly higher OxA levels than normal (63.42 ± 37.56 vs. 54.84 ± 23.95 pg/mL) [157]. Studies suggested that transcranial repetitive needle stimulation may alleviate post-stroke sleep disorders by reducing serum OxA levels [157,158].…”
Section: Neurotransmitter Regulationmentioning
confidence: 99%